Alterations in prostate morphogenesis in male rat offspring after maternal exposure to Di-n-butyl-phthalate (DBP) - de Mello Santos, Talita [UNESP]; da Silveira, Lívia Teresa Ribeiro [UNESP]; Rinaldi, Jaqueline Carvalho [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Domeniconi, Raquel Fantin [UNESP] (Elsevier, 2017)
Prostate morphogenesis is regulated by androgens hormones and modulated by morphogenetic proteins such as Bone Morphogenetic Proteins (BMPs). This study aims to investigate the effects on prostate development in male offspring and differentiation after gestational and lactational maternal exposure to Di-n-butyl-phthalate (DBP), an important environmental contamination. Pregnant Wistar rats received 100 or 500 mg/kg of DBP (DBP100 and DBP500), by gavage, from gestation day 15 (GD15) until postnatal day 21 (PND21). The pups were euthanized on PND1 and PND21. Anogenital distance and testosterone levels decreased in animals from exposed mothers (DBP100 and 500) on PND1. A three-dimensional reconstruction model of the prostatic urethra showed reduction in the prostatic buds in the DBP500 group. AR expression and α-actin immunoreactivity decreased, and BMP-4 expression was lower on PND1 for DBP500. These results showed that DBP exposure, especially at a higher dose, delayed prostate morphogenesis by reducing the testosterone/AR axis and BMP-4 expression.
Keywords: Androgen receptor; Antiandrogenic; Di-n-butyl-phthalate (DBP) BMP-4; Prostate development; Testosterone; α-actin